NSERC Funding of Earth Sciences Research in Canadian Universities: Current Status and Opportunities - Hall, Jeremy (Geoscience Canada, 1999)
Summary This article outlines current funding of geoscience research by the Natural Sciences and Engineering Research Council of Canada (NSERC), and opportunities for enhancing researchers' access to its programs, especially the University-Industry Program.